A Retrospective Impact Evaluation of the Tamil Nadu Empowerment and Poverty Alleviation (Pudhu Vaazhvu) Project - Khanna, Madhulika; Kochhar, Nishtha; Palaniswamy, Nethra (Taylor and Francis, 2015)
Community based livelihood interventions, which focus directly on increasing income and employment, have become an increasingly important component of large-scale poverty reduction programmes. We evaluate the impact of a participatory livelihoods intervention – the Tamil Nadu Empowerment and Poverty Reduction (Pudhu Vaazhvu) Project (PVP) using propensity score matching methods. The paper explores the impact of PVP on its core goals of empowering women and the rural poor, improving their economic welfare, and facilitating public action. We find significant effects of PVP on reducing the incidence of high cost debt and diversifying livelihoods. We also find evidence of women’s empowerment, and increased political participation.